Los cuentos infantiles y el lenguaje oral en niños de 4 a 5 años del Centro de Educación Inicial Pío Jaramillo Alvarado de la ciudad de Loja, periodo 2023-2024. - Lozano Alvarado, Abigail Elizabeth (2024)
As one of the most efficient means of conveying messages, oral language plays a significant role in reaching other people and establishing emotional bonds that facilitate interactions with one another and peer relationships. It is for this reason that adequate stimulation from the onset of life is critical, which allows to ensure a normal development and according to their age, thus directly contributing to the acquisition of skills. This work proposes the following general objective: To demonstrate how children's stories can aid in the development of oral language in children aged 4 to 5, at Pío Jaramillo Alvarado Early Education Center in the city of Loja in the period 2023-2024. The study used a mixed approach, with a non-experimental design, a descriptive scope and the following methods: inductive, deductive, analytical and synthetic. In order to assess the level of oral language, a revised Navarre oral language test (PLON-R) was used. According to the results, 13.64 % of children had a normal development of their communication skills, 13.64 % needed to improve their communication skills, and 72.73% had a delayed level of oral language. In view of these results, a guide of activities based on children's stories called “Telling Stories” aims to develop oral language skills. Several previous studies have demonstrated that children's stories provide a didactic and interactive tool for developing communicative skills, which allows infants to express their opinions and emotions clearly, thus contributing to their academic and family development. Key words: Children's stories, initial education, interaction, oral language.